(untitled) (Revista da Faculdade de Direito, Universidade de São Paulo, 2010)
In a large synthesis, we offer, in this study, the linies of the reform of the law studies under Justinian with basis in the informations done by the constitutio “Omnem”, from 533 A. D., addressed to law professors of Constantinople and Beyrouth schools, and also the general caracteristics of some methods of transmition of the compilated law by the “antecessores”, who taught in the period from 533 to 565 A. D.